(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
This paper examines Muslim women’s right to jointly acquire property after divorce and the issues that arise from the Sharia perspective. Similarly, in Malaysia, where Islam is the religion of the Federation, the rights of Muslim women are protected under the Islamic Family Law Act and Enactments of each state. Additionally, it is simpler for Muslim women to assert their entitlement to jointly acquired property when a divorce occurs. Yet, many still do not do so because they are unaware of their rights under Sharia and Islamic law. This paper will use the method of a desk review of Malaysian laws and policies and Sharia sources, including the interpretations of the Quran and Sunnah, fatwas, and writings of Islamic scholars on the subject. This paper discovered that there are still many instances where divorced women are left to address their marriage issues on their own and are often unaware of their rights to acquire property after the divorce jointly. Hopefully, this paper will shed some light on Muslim women’s rights to jointly acquire property in Malaysia.